FENOMENA BUDAYA MASYARAKAT ACEH TERHADAP PERILAKU PEMBERIAN ASI EKSKLUSIF - Cut Andyna (Aceh Anthropological Journal, 2022)
Breastfeeding to infants have a positive impact on their health. But not all women understand the importance of breastfeeding for babies. Various aspects affect, including the cultural factors that are still so dominant among the people of Aceh. This research was conducted with a phenomenological qualitative approach in Aceh Province to examine the cultural phenomenon of the decision to breastfeed. The results showed that the cultural aspect influenced the mother's decision to breastfeed babies exclusively. Understanding mothers and those around them and the lack of information and education from local health workers to educate from pregnancy to postpartum is the dominant factor for breastfeeding mothers not to breastfeed exclusively. Besides giving formula milk, other foods such as bananas and filtered porridge are given before entering the MPASI period, which should be at the age of 6 (six) months. Therefore, it is necessary to continue socialization and complete so that public knowledge increases according to the expectations of the government, which has strived and launched programs related to exclusive breastfeeding by paying attention to points that the community has not fully understood.Abstrak: Pemberian ASI pada bayi memberikan dampak positif bagi kesehatannya. Namun tidak semua wanita memahami pentingnya ASI bagi bayi. Berbagai aspek mempengaruhi, termasuk faktor budaya yang masih begitu dominan di kalangan masyarakat Aceh. Penelitian ini dilakukan dengan pendekatan kualitatif fenomenologi di Provinsi Aceh untuk mengkaji fenomena budaya keputusan menyusui. Hasil penelitian menunjukkan bahwa aspek budaya mempengaruhi keputusan ibu untuk menyusui bayi secara eksklusif. Pemahaman ibu dan orang di sekitarnya serta kurangnya informasi dan edukasi dari petugas kesehatan setempat untuk mengedukasi sejak hamil (antenatal) hingga nifas (pasca melahirkan) menjadi faktor dominan ibu menyusui untuk tidak memberikan ASI eksklusif. Selain pemberian susu formula, makanan lain seperti pisang dan bubur saring diberikan sebelum memasuki masa MPASI yang seharusnya pada usia 6 (enam) bulan. Oleh karena itu perlu terus dilakukan sosialisasi dan lengkap agar pengetahuan masyarakat meningkat sesuai harapan pemerintah yang telah mengupayakan dan mencanangkan program-program terkait ASI eksklusif dengan memperhatikan poin-poin yang belum sepenuhnya dipahami masyarakat.